2019
DOI: 10.25035/ijare.10.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Boating Incidents in Inuvik, Northwest Territories, Canada

Abstract: Injury prevention programs that focus on boating and water safety in the Northwest Territories (NWT) have existed for decades; however, rates of boating incidents are much higher in the NWT than southern Canada. To better understand this health disparity, we engaged in community-based participatory research informed by postcolonial feminist theory to examine Aboriginal men's understandings of the risk factors that contribute to boating incidents in Inuvik, NWT. Participants identified four main risk factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…1,8,9,12 Indeed, scholars have found that some men do not wear lifejackets because they want to avoid appearing unskilled or "less manly". 13 Some may assume that men who do not identify with hegemonic masculine values would be unlikely to participate in risky behaviours. Importantly, this ignores how men who do not display hegemonic masculinity can be censured by their peers.…”
Section: Ma Sculinit Y and Life Jack E T Us Ementioning
confidence: 99%
See 1 more Smart Citation
“…1,8,9,12 Indeed, scholars have found that some men do not wear lifejackets because they want to avoid appearing unskilled or "less manly". 13 Some may assume that men who do not identify with hegemonic masculine values would be unlikely to participate in risky behaviours. Importantly, this ignores how men who do not display hegemonic masculinity can be censured by their peers.…”
Section: Ma Sculinit Y and Life Jack E T Us Ementioning
confidence: 99%
“…Such behaviours can be described as “hypermasculine” displays 11 that align with hegemonic masculine ideals that assert that men should not be afraid of danger 1,8,9,12 . Indeed, scholars have found that some men do not wear lifejackets because they want to avoid appearing unskilled or “less manly” 13 . Some may assume that men who do not identify with hegemonic masculine values would be unlikely to participate in risky behaviours.…”
Section: Masculinity and Lifejacket Usementioning
confidence: 99%